Prevalensi dan Intensitas Ektoparasit Pada Anjing Peliharaan (Canis familiaris) di Kalimantan Timur, Indonesia - Berty Veibrita Sinaga; Nova Hariani (Jurnal Bioterdidik: Wahana Ekspresi Ilmiah, 2019)
The closeness of a pet dog to humans is causes his health condition to need attention. One of parameter on dog health disorders is the presence of ectoparasites in the body. The purposes study were to know of ectoparasites are found in pet dog populations. The method used is a survey and directly collection of ectoparasites at 30 pet dogs. The results of study obtained are 4 species of ectoparasites that attack pet dogs are namely Ctenocephalides canis, Boophilus sp., Trichodectes canis and Rhipicephalus sanguineus. The prevalence of ectoparasites in the acquired pet dog population is Ctenocephalides canis which is 90%, Rhipicephalus sanguineus 67%, Trichodectes canis 57% and the lowest in Boophilus sp. 43.3%. The ectoparasites intensity in the pet dog population obtained was Trichodectes canis 22 ind/dog, Ctenocephalides canis 8 ind/dog, Rhipicephalus sanguineus 4 ind/dog and Boophilus sp. are 3 ind/dog. Kedekatan anjing peliharaan dengan manusia menyebabkan kondisi kesehatannya perlu diperhatikan. Salah satu parameter gangguan kesehatan anjing adalah keberadaan ektoparasit dalam tubuh. Tujuan penelitian adalah untuk mengetahui ektoparasit yang ditemukan pada populasi anjing peliharaan. Metode yang digunakan adalah survei dan pengumpulan langsung ektoparasit pada 30 anjing peliharaan. Hasil penelitian yang diperoleh adalah 4 spesies ektoparasit yang menyerang anjing peliharaan yaitu Ctenocephalides canis, Boophilus sp., Trichodectes canis dan Rhipicephalus sanguineus. Prevalensi ektoparasit pada populasi anjing peliharaan yang diperoleh adalah Ctenocephalides canis yang 90%, Rhipicephalus sanguineus 67%, Trichodectes canis 57% dan terendah di Boophilus sp. 43,3%. Intensitas ektoparasit pada populasi anjing peliharaan yang diperoleh adalah Trichodectes canis 22 ind/dog, Ctenocephalides canis 8 ind/dog, Rhipicephalus sanguineus 4 ind/dog dan Boophilus sp. adalah 3 ind/dog. Kata kunci: anjing peliharaan, ektoparasit, Muara Badak